Chapter Servizi ecosistemici in chiave progettuale e proattiva - Franchina, Alice (Territori, 2020)
Having ascertained that the ecosystem service paradigm is a scientific rather than a "natural" one, the text criticizes the purely analytical attitude with which it is usually used; such an attitude, together with the dominance of a purely economic evaluation, is hiding the risk of a real commodification of nature. This highlights the need to progress towards the use of the ecosystem service instrument within a transformative design framework, aiming at social equity, and which adopts an inclusive evaluation system of the local actors.